The future of antibiotics and meat - Raphaely, Talia; Marinova, Dora; Marinova, M. (IGI Global, 2017)
© 2017 by IGI Global. All rights reserved.This chapter discusses antibiotic use in the livestock industry and potential ramifications for human health. Antibiotics are routinely administered to food animals, primarily at sub-therapeutic levels. The extensive use of antibiotics in global animal husbandry in quantities greater than used for humans is creating antibiotic resistance. There is evidence that antibiotic resistant organisms emerging in food animals transfer to humans through the food chain, environmental contamination, direct association with animals or through mobile resistant genetic elements resulting in co-resistance to other antibiotics. No new classes of antibiotics have been developed since the 1980s. Intensifying use of existing antibiotics for meat production poses new challenges for treating humans, needs to be taken seriously and dealt with urgently. This chapter argues that reduced meat consumption is an under-considered but essential part in any suite of solutions aimed at preserving the use of antibiotics for human treatment.